Phy Simulation Model Of The Ieee 802.11ah - Jurák, Petr (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2018)
This paper presents a MATLAB-based IEEE 802.11ah simulation model. This short article starts with a brief introduction to the IEEE 802.11ah standard. After that, the complete Tx block (on physical layer level) of the IEEE 802.11ah system is described. It is completely realized in the MATLAB program environment. Finally, its correctness is verified by several simulations.
Keywords: Wi-Fi; IEEE 802.11ah; IoT; PHY; simulation model; RF spectrum; BER; SNR